Apakah Keadilan Formal Penilaian Kinerja Menjadi Determinan Kepuasan Kerja dan Komitmen Continuance? - Majang Palupi (Universitas Mercu Buana, 2021)
The role of formal justice becomes the dominant aspect in explaining employee attitudes and behavior in the organization. The purpose of this study is to investigate formal justice which consists of distributive and procedural justice in explaining job satisfaction and continuance commitment in organizations. The respondents of this study are employees from private small and medium business sector. The number of questionnaires obtained and could be used as many as 215 questionnaires. Hypothesis test results show that there is a significant positive relationship between procedural justice toward job satisfaction and also continuance commitment through job satisfaction, whereas distributive justice positively influences continuance commitment. Other result shows job satisfaction positively effects continuance commitment. As such, formal justice fulfills its importance of explaining job satisfaction and continuance commitment while job satisfaction is largely in mediating the effect of formal justice on continuance commitment.